Impact of a post-partum family planning intervention on contraception and fertility in Tanzania: two-year follow-up of a cluster-randomised controlled trial - Rohr, Julia K.; Huber-Krum, Sarah; Rugarabamu, Angelica; Pearson, Erin; Francis, Joel M.; Guo, Muqi; Siril, Hellen; Shah, Iqbal; Canning, David; Ulenga, Nzovu; Bärnighausen, Till (The European journal of contraception & reproductive health care, 2024)
We evaluate contraceptive use and pregnancy two years following an intervention in Tanzania, which provided antenatal post-partum family planning counselling and post-partum intrauterine device (PPIUD) services following delivery.
Gesehen am 18.03.2024